Pencarian Rute Terpendek Menggunakan Algoritma Dijkstra dan Astar (A*) pada SIG Berbasis Web untuk Pemetaan Pariwisata Kota Sawahlunto - Pugas, Diana Okta; Somantri, Maman; Satoto, Kodrat Iman (Transmisi, 2011)
Geographic information systems related to the position of objects in the earth's surface such as the position of the attractions that are connected with roads. Streets that are interconnected to form a complex network. Usually people use our manual to find the shortest route of an object toward a particular object but it is less than optimal because it requires precision and a long time. The shortest route search problem has been solved by several algorithms such as Dijkstra's algorithm, Astar, Floyd Warshall, Ant Colony and others. Based on this final task is to discuss the implementation of the shortest route to the geographic information system of tourism in a city using the distance parameter. City to be addressed is Sawahlunto has 12 attractions that are connected with road network. Shortest path search algorithm used is Dijkstra's and Astar algorithm. Geographic information system of tourism is displayed in a web form, with the programming language PHP, database PosgreSQL and support PostGIS and pgRouting. Based on the testing of these applications can provide the shortest route along the travel distance to and from 12 tourist sites in Sawahlunto. Astar algorithm is faster in the process of finding the shortest route instead of Dijkstra's algorithm with an average gap of 40 ms. Application also provides information supporting the tourism profile information, attractions, culture, and contacts. Keyword : shortest path, Dijkstra algorithm, Astar algorithm, geographic information system